Family Planning Communities in Pemogan Using WHO Community Engagement Model - Dinar Saurmauli Lubis; I.A. Kharisma Dyah Intan Maharani (Universitas Airlangga, 2022)
Communities is an area unit at the village level with criteria in which there is an integration of the Family Planning Population and Family Development program and related sectors to improve the quality of family and community life. The formulation of the research problem is how the village community is engaged in the family planning communities program in Pemogan Village Denpasar. Objective: The objective of this research is to find out the involvement of the village community in the family planning communities program. Methods: This study used a qualitative descriptive research design and was conducted from April to May 2021. This research applied the World Health Organization (2012) framework on community engagement by identifying the level in involvement of inform, consult, involve, collaborate, and shared leadership. There were 9 informants which consisted of the head of Pemogan Village Denpasar, educators of family planning, cadres of family planning communities, and community groups with inclusion criteria. Data collection methods used focus group discussion, in-depth interviews, and document analysis. Data were analyzed with thematic data reduction, data presentation, and conclusion. Data validation used triangulation of sources and methods, peer debriefing, and member checking. Results: This study found that the community has been a part of the family planning communities program. Community engagement level in the family planning communities program is at the involve level and less in informing the program and leadership. Conclusion: Community engagement in the family planning communities program in Pemogan Village includes the level of inform, consult, involve, collaborate, and shared leadership. This research suggests the village government increase space for the community to be engaged as a partner in implementing activities and shared leadership through cadre empowerment and socialization.